2009
DOI: 10.1590/s0006-87052009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de cultivares de antúrio IAC como plantas de vaso no norte do Paraná

Abstract: LÚCIA SADAYO ASSARI TAKAHASHI ( 2* ); RICARDO TADEU FARIA ( 2 ); ANTONIO FERNANDO CAETANO TOMBOLATO ( 3 ); FRANCINE LORENA CUQUEL ( 4 ); MAURÍCIO LUIZ GROSSI ( 5 ) RESUMOO gênero Anthurium Schott. (Araceae) compreende mais de 600 espécies. Todas são ornamentais e se destacam pela beleza da folhagem. A espécie Anthurium andraeanum Lind. tem a preferência dos consumidores como planta ornamental devido ao tamanho e colorido de suas espatas. O objetivo do trabalho foi avaliar o desenvolvimento, em vaso, de cinco c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
3
1
0
1
Order By: Relevance
“…In the other months the cultivars Kinã, nK 102 and Terena produced longer spadices (Table 2). These results agree with those obtained by Takahashi et al (2009) Statistically significant differences were found for spathe length (Table 3) in all assessments; the cultivars Kinã, nK 102 and Terena had the highest means, due to the length and width of the spadix. Takahashi et al (2009) observed the largest spathes and spadices in 'Terena', followed by 'Rubi', 'Apalai', and 'Parakanã'.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In the other months the cultivars Kinã, nK 102 and Terena produced longer spadices (Table 2). These results agree with those obtained by Takahashi et al (2009) Statistically significant differences were found for spathe length (Table 3) in all assessments; the cultivars Kinã, nK 102 and Terena had the highest means, due to the length and width of the spadix. Takahashi et al (2009) observed the largest spathes and spadices in 'Terena', followed by 'Rubi', 'Apalai', and 'Parakanã'.…”
Section: Resultssupporting
confidence: 90%
“…These results agree with those obtained by Takahashi et al (2009) Statistically significant differences were found for spathe length (Table 3) in all assessments; the cultivars Kinã, nK 102 and Terena had the highest means, due to the length and width of the spadix. Takahashi et al (2009) observed the largest spathes and spadices in 'Terena', followed by 'Rubi', 'Apalai', and 'Parakanã'. According to these authors, among the tested cultivars, Terena showed the best characteristics for pot cultivation due to its longer spathes and shorter floral stems.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A família Araceae faz parte das monocotiledôneas herbáceas, que inclui 118 gêneros e cerca de 3.437 espécies, no Brasil existem 691 espécies catalogadas até o ano de 2015 (COELHO et al, 2015), com hábitos terrícolas, rupícola, epífita, hemiepífita e hemiparasita (COELHO et al, 2015;MAYO et al, 1997). Apresenta ampla distribuição, no entanto, têm maior ocorrência em região dos trópicos úmidos, pois não suporta condições extremas, ocorrendo de forma mais numerosa nas Américas, no Sudeste Asiático, na África, no Arquipélago Malaio, na Eurásia e nas Ilhas Seychelles (MAYO et al, 1997;TAKAHASHI et al, 2009). As espécies da família apresentam amplo potencial econômico, sendo exploradas como ornamentais e alimentícias (MAYO et al, 1997).…”
Section: Introductionunclassified